2019
DOI: 10.1044/2019_jslhr-l-rsnp-19-0219
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Recovery of Sentence Processing in Aphasia

Abstract: Purpose Reorganization of language networks in aphasia takes advantage of the facts that (a) the brain is an organ of plasticity, with neuronal changes occurring throughout the life span, including following brain damage; (b) plasticity is highly experience dependent; and (c) as with any learning system, language reorganization involves a synergistic interplay between organism-intrinsic (i.e., cognitive and brain) and organism-extrinsic (i.e., environmental) variables. A major goal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 177 publications
(203 reference statements)
0
8
0
4
Order By: Relevance
“…As summarized in the introduction, several lesion, fMRI and DTI studies have provided evidence that left IFG plays a pivotal role in sentence comprehension due to its position that comprises both areas of semantic selection (BA 45/47) through the ventral language route, as well as areas of hierarchical ordering of syntactic phrases (BA 44) through the dorsal language route [27,29,31,32,49]. Although the evidence in PPA for sentence processing is more in favor of the dorsal route [30,50], probably due to the type of sentences studied, the involvement of the left frontal operculum is indisputable [30,33]. The present study provides strong evidence not only on the role of the left IFG in sentence comprehension in PPA but also on the causal involvement of the left IFG (with its semantic and syntactic computations) in sentence comprehension and its rehabilitation in a neurodegenerative condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in the introduction, several lesion, fMRI and DTI studies have provided evidence that left IFG plays a pivotal role in sentence comprehension due to its position that comprises both areas of semantic selection (BA 45/47) through the ventral language route, as well as areas of hierarchical ordering of syntactic phrases (BA 44) through the dorsal language route [27,29,31,32,49]. Although the evidence in PPA for sentence processing is more in favor of the dorsal route [30,50], probably due to the type of sentences studied, the involvement of the left frontal operculum is indisputable [30,33]. The present study provides strong evidence not only on the role of the left IFG in sentence comprehension in PPA but also on the causal involvement of the left IFG (with its semantic and syntactic computations) in sentence comprehension and its rehabilitation in a neurodegenerative condition.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to treatment, a recent single-case treatment study employing a syntactic intervention on a patient with non-fluent PPA showed improvement of his production and comprehension of non-canonical (passive and object cleft) sentences with upregulation of his frontal network [33]. Additionally, two tDCS studies in healthy controls have provided evidence for the causal involvement of the left IFG in syntactic computations [34,35].…”
Section: Involvement Of the Left Ifg In Sentence Comprehension: Syntamentioning
confidence: 99%
“…S lingvističkog aspekta pacijenti s Brokinom afazijom ispoljavaju najveće deficite u oblasti morfologije i sintakse. Oni se uglavnom izražavaju sintaksički pojednostavljenim rečenicama, u kojima se uočava izmenjen redosled reči, nedostatak ili pogrešna upotreba funkcionalnih reči i/ili vezanih morfema (Kearns, 1997;Thompson, 2019;Vuković 2016). Kao posledica javlja se agramatizam, koji inače predstavlja centralni simptom Brokine afazije (Vuković 2002(Vuković , 2016.…”
Section: Uvodunclassified
“…Osim imenica i punoznačnih glagola, u našem jezičkom korpusu identifikovan je manji broj zamenica i priloga, dok su ostale vrste reči jedva primetne. Ovi nalazi pokazuju da se, u pogledu upotrebe pojedinih vrsta reči, ispitanici s agramatičkom afazijom koji govore srpski jezik ne razliku bitno od ispitanika koji govore engleski jezik (Lee & Thompson, 2004;Thompson, 2019). Naši rezultati pokazuju da u govornom jeziku pacijenata s Brokinom afazijom dominiraju imenice.…”
Section: Diskusijaunclassified
“…Sung 2017 (Im, 2007;Nam, 1988 (Hula & McNeil, 2008;Murray, 2012;Murray & Kean, 2004), 알츠하이머 치매 환자의 문장 산출 능력을 본 다른 선행연구에서도 알 수 있다 (Altmann, 2004;Atmann, Kempler, & Andersen, 2001;Bates, Harris, Marchman, Wulfeck, & Kritchevsky, 1995). 이는 문장을 처리할 때, 문장 내 논 항 구조에 맞게 의미역을 파악하여 의미론과 통사론적 형태를 연 결 짓는 능력(mapping)이 필요하여 ) 인지적 부담이 가중되기 때문이며 (Friederici & Frazier, 1992), 통합적인 인지 과정을 필요로 하기 때문이다 (Carlson & Frazier, 1983;Carlson & Tanenhaus, 1988;Rayner et al, 1983;Thompson, 2019). 또한 실어증 환자들이 문장 내에서 명사를 의미 적으로 표상(semantic representation)하는데 어려움을 보이고 의 미역 배열에 손상을 보이며 (Webster, Franklin, & Howard, 2007) 어휘-의미론적 정보(lexical semantic information)에 해당하는 문 법형태소에 어려움을 보이는 것을 통해 (Levelt, 1989) (Nam, Yim, Jung, Kim, & Pyun, 1999 (Fillmore, 1968;Jackendoff, 1972 Tanenhaus, 1988;Rayner et al, 1983).…”
unclassified